USAGE OF NON MEDICATED METHODS FOR CHILDREN'S BRONCHIAL ASTHMA THERAPY - E.A. Vishneva; A.A. Alekseeva; L.S. Namazova; L.M. Ogorodova; M.A. Khan; O.M. Konova ("Paediatrician" Publishers LLC, 2007)
The article analyzes current situation of bronchial asthma non medicated therapy. The need to apply such therapy is associated with the on going trend of more frequent severe bronchial asthma cases, as well as not always efficient standard schemes of medicated treatment. The authors announce a physiotherapy device «aster» - it is based on innovative technologies and designed for noninvasive impact of electromagnetic waves with non thermal intensity upon the «pulmonary triangle» body area. A randomized multicentered survey of Russia's pediatricians union is being conducted to prove the efficiency of this device for children with bronchial asthma and basic therapy adequate to the severity degree. The application of this device is expected to reduce symptoms and eliminate dysfunctions of respiratory system typical for bronchial asthma, which cannot be totally eliminated with the current anti inflammatory agents.Key words: bronchial asthma, non medicated therapy.